INDUSTRIALISASI BERBASIS SYARIAH BAGI MASYARAKAT PERKOTAAN (STUDI PERUSAHAAN AIR KHAIRA DI YOGYAKARTA) - Prakoso, Tjahyo Adji (UNIVERSITAS SEBELAS MARET (UNS), 2020)
Urban communities, have needs that can be said to be all-round, such as clothing, food and shelter needs, including water needs, almost all the needs of living things are inseparable from water, including for urban communities. On the other hand, this is an opportunity for industrialization commodities, such as drinking water industry, this research is focused on the company drinking water industry in Yogyakarta, the KHAIRA company which has the concept of sharia-based industrialization which is realized in the vision of